Improving delivery of health care to Aboriginal and Torres Strait Islander children. (2nd November 2014) - Attwood, Lucy; Rodrigues, Sarah; Winsor, Josephine; Warren, Shirley; Biviano, Lyn; Gunasekera, Hasantha
<x xml:space="preserve">Abstract</x> Aim To identify opportunities to improve health‐care delivery for urban Aboriginal and Torres Strait Islander children requiring hospital admission and to determine their characteristics. Methods We analysed all documentation of admissions of Aboriginal and/or Torres Strait Islander children to a tertiary paediatric hospital in 2010. We reviewed the medical records to determine whether the Aboriginal status of patients was known, whether Aboriginal and/or Torres Strait Islander children and their families were reviewed by Aboriginal staff during admission and whether basic health‐care quality indicators were met, including documentation of anthropometry, ear examination findings, immunisation status and catch‐up immunisation delivery. Results In 2010, 543 (2%) patients admitted to the institution were identified as Aboriginal and/or Torres Strait Islander: 140/538 (26.0%) were from the first decile (most disadvantaged) on Socio‐Economic Indexes for Areas index. Of all admitted children, 148/543 (27.3%) were referred to Aboriginal health professionals during admission, more when length of stay was greater than 7 days (61% vs. 23%, P < 0.001). There was documentation of weight in 533/543 (98.2%), ear examinations in 64/543 (11.8%), immunisations being not up to date in 126/543 (23%), catch‐up immunisation given in 7/126 (5.6%), Aboriginal and/or Torres Strait Islander status in 8/543 (1.5%) medical and 1/543 (0.2%) nursing discharge summaries. Conclusions We have identified several opportunities to improve culturally appropriate health‐care delivery for Aboriginal and Torres Strait Islander children admitted to hospital, including improved recognition of Aboriginal and/or Torres Strait Islander status of patients, improved access to Aboriginal health professionals and increased performance and documentation of basic anthropometry, ear examination and immunisation catch‐up.